2015
DOI: 10.4172/2329-6925.1000203
|View full text |Cite
|
Sign up to set email alerts
|

Successful 36 Months Result of Debranching TEVAR for Kommerell?s Diverticulm with the Aberrant Left Subclavian Artery

Abstract: A case of successful endovascular repair of right aortic arch with the aberrant left subclavian artery (ALSA) arising from Kommerell's diverticulum (KD). Our strategy consisted of coil embolization for the orifice of the ALSA, put the bypass between left common carotid artery and left subclavian artery and exclusion of KD by stent graft insertion. Enhanced computed tomography scan 36 months after the operation showed successful exclusion of KD, patency of the bypass graft, and no evidence of endoleak.Endovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 10 ) Furthermore, Takai et al reported stent grafting for Kommerell’s diverticulum using a common carotid artery to left subclavian artery bypass and stent graft placement via the descending aorta and not via the aortic arch. 9 ) In our patient, Kommerell’s diverticulum branched near the aortic arch, and a procedure similar to that described Takai et al would not have secured a sufficient proximal landing zone, thus conferring a high risk of endoleak. To secure a sufficient landing zone on the side of the lesser curvature and to prevent bird’s beak, we first constructed a bypass between the right common carotid artery and the right subclavian artery using a blood vessel prosthesis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 10 ) Furthermore, Takai et al reported stent grafting for Kommerell’s diverticulum using a common carotid artery to left subclavian artery bypass and stent graft placement via the descending aorta and not via the aortic arch. 9 ) In our patient, Kommerell’s diverticulum branched near the aortic arch, and a procedure similar to that described Takai et al would not have secured a sufficient proximal landing zone, thus conferring a high risk of endoleak. To secure a sufficient landing zone on the side of the lesser curvature and to prevent bird’s beak, we first constructed a bypass between the right common carotid artery and the right subclavian artery using a blood vessel prosthesis.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, stent grafts have been used in the treatment of Kommerell’s diverticulum, and cases are occasionally reported. 2 , 9 ) The anatomy of this patient included a steeply angled aortic arch and branching of Kommerell’s diverticulum relatively close to the top of the aortic arch. The branching of the right subclavian artery also originated from the ascending aorta close to the top of the aortic arch.…”
Section: Discussionmentioning
confidence: 99%